La cultura organizacional y la gestión de los servicios en la municipalidad provincial de Trujillo - Chávez Abanto, Dante (2010)
Was investigated the influence of organizational culture in the management of public services provided by the Provincial Municipality of Trujillo. The organizational culture has become an element of strategic importance relieved in organizations, it is a strength that leads to the organizations to excellence and to succeed, and consists of shared values and beliefs that develop within an organization that guides the behavior of its members, which distinguish it one from another. The sample consisted of 196 workers permanent employees, whose size has been determined by the investigator based on the following criteria: to allow prioritizing the level of depth in research, the size of the population, the relative knowledge and experience of local realities and, the nature and limitations of the study. Factors affecting the organizational culture were indistinguishable from individual securities practice, lack of organizational values, lack of commitment and identification with the institution, lack of teamwork, training, organizational structure, goals and objectives institutional as well as the existence of an unfavorable organizational climate can not adequately provide public services to the Provincial Municipality of Trujillo.